2019
DOI: 10.1097/cm9.0000000000000345
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of prognosis in Talaromyces marneffei infections with respiratory system lesions

Abstract: Background: Little study has investigated the differences between Talatomyces marneffei ( T. marneffei ) respiratory infection and tuberculosis and the prognostic factors of such infection. This study investigated the characteristics and prognostic factors of T. marneffei infections with respiratory lesions and the causes of misdiagnosis. Methods: Clinical characteristics and prognoses of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…However, it was later reported in patients with other immunodeficiencies such as autoimmune diseases, solid organ or hematopoietic stem cell transplantation, hematology, and those receiving novel targeted therapies ( Wang et al., 2003 ; Woo et al., 2005 ; Chan et al., 2013 ; Chan et al., 2015 ; Lei et al., 2018 ). T. marneffei infection involves multiple organ systems, such as the lungs, skin, bone marrow, digestive system, and disseminated infections ( Samson et al., 2011 ; Qiu et al., 2019 ). Amphotericin B, itraconazole, voriconazole, and posaconazole are effective in the management of T. marneffei infection ( Lei et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was later reported in patients with other immunodeficiencies such as autoimmune diseases, solid organ or hematopoietic stem cell transplantation, hematology, and those receiving novel targeted therapies ( Wang et al., 2003 ; Woo et al., 2005 ; Chan et al., 2013 ; Chan et al., 2015 ; Lei et al., 2018 ). T. marneffei infection involves multiple organ systems, such as the lungs, skin, bone marrow, digestive system, and disseminated infections ( Samson et al., 2011 ; Qiu et al., 2019 ). Amphotericin B, itraconazole, voriconazole, and posaconazole are effective in the management of T. marneffei infection ( Lei et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Amphotericin B, itraconazole, voriconazole, and posaconazole are effective in the management of T. marneffei infection ( Lei et al., 2018 ). Unfortunately, the mortality rate of T. marneffei infection is very high, especially for non-AIDS patients due to delayed diagnosis ( Le et al., 2011 ; Lee et al., 2012 ; Lei et al., 2018 ; Qiu et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Common clinical features of T.M infection among these non-HIV-infected patients include fever, malaise, weight loss, skin and soft tissue lesions, hepatosplenomegaly, lymphadenopathy, cough, and dyspnea 1. T.M infection is associated with high mortality because it is commonly misdiagnosed during the early stages of the disease 2. Moreover, secondary hemophagocytic lymphohistiocytosis (SHLH),3 a rare clinical syndrome characterized by hyperinflammatory responses, high morbidity, acute onset, rapid progression, and high mortality, occurs as a comorbidity with other infections, particularly Epstein-Barr virus (EBV) and bacterial infections 4.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study conducted in Shanghai (unfortunately with a relatively small sample size) indicated that low C0D4 + T‐cell counts and low haemoglobin levels were associated with higher mortality of talaromycosis among HIV‐infected patients 11 . A recent study indicated that CD4 + T‐cell counts and CD4+/CD8 + ratios are critical determinants of prognosis in T. marneffei ‐infected patients with respiratory system lesions 12 . However, most patients in these cohorts had CD4 + T‐cell counts less than 50 cells/μL, and there was no statistically significant difference in CD4 + T‐cell counts between the survival group and the non‐survival group.…”
Section: Discussionmentioning
confidence: 98%